The Effect of Exhaust Gas Recirculation (EGR) on the Emission of a Single Cylinder Spark Ignition Engine - Limyaa Mahdi Asaad; Sajda Sabri Faris; Muntaha Hameed Ebraheem (Tikrit Journal of Engineering Sciences, 2016)
A single cylinder variable compression ratio spark ignition engine type PRODIT was used in this study. The experiments were conducted with gasoline fuel (80 octane No.)at equivalence ratio (Ø =1). This study examined the effects of exhaust gas recirculation on emission. It was conducted at engine speeds (1500, 1900, 2300 and 2700 r.p.m.). The exhaust gases were added in volumetric ratios of 10%, 20% and 30% of the entering air/fuel charge. The results showed that the EGR addition decreases the CO2 concentrations, in the same time CO and HC concentrations increase remarkably. NOx concentration decreased highly with the increase of EGR percentage at variable engine speeds and constant torque. Also, it decreased when the engine run at constant speed and variable engine torque. The exhaust gas temperature decreased with increasing EGR ratio.